On the Spectral Expansions Connected with Schrödinger’s Operator of Continuous Functions in a Closed Domain - Abdumalik A. Rakhimov; Kamran Zakaria; Nazir Ali Khan (Journal of Basic & Applied Sciences, 2012)
Present paper is devoted to study of uniformly convergence of spectral expansions in a closed domain. We consider here as a spectral expansions eigenfunction expansions connected with one Schrodinger’s operator with singular potential in two dimensional domains with smooth boundary.